A CRISE ENERGÉTICA E O ENSINO TÉCNICO PROFISSIONALIZANTE - Ferreira, Jorge Luiz (Revista Liberato, 2013)
The nowaday energy crisis is just the beginning of a process that will get worse in few years, considering not only the relative aspects to the shortage of the production sources as well as the environment damages. The lack of an energy policy for our country can become this process much more serious besides influencing on the economical process dependence of other nations. It's indispensable to begin an understanding process in the courses that graduate future technicians. On the other hand it's really important to develop the rationalization as well as the integration of energy resources in the production processes and energy consumption in the industry, trade and residences.